Student Motivation In Class VII Educational Learning At Smp Negeri 10 Pekanbaru - Ridwan Nasution; Oki Candra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to determine the level of student motivation in Physical Education Class VII learning at State Junior High School 10 Pekanbaru. This research is quantitative research, the method used is a descriptive method with a survey type. The population in this study was class VII students at Pekanbaru 10 State Middle School, totaling 279 students. The sampling technique uses total sampling technique. The instrument used in this research used a Likert scale or questionnaire method which was distributed to respondents. Based on research results, Student Motivation in Class VII Physical Education Learning is classified as Very High, this can be seen in the percentage results of 83% which are in the assessment range of 81%-100% with Very High criteria .